Genetically modified organisms and sustainable development goals: A survey of Taiwanese public opinion - Shin-Cheng Yeh; Pei-Xuan Chen; Chih-Cheng Lin; I-Chun Chiang (PLoS ONE, 2025)
This study investigates public opinion of genetically modified organisms (GMOs), the role of GMOs in achieving the Sustainable Development Goals (SDGs), and economic preferences in Taiwan. A survey of 977 Taiwanese adults assessed their knowledge, attitudes, and willingness to pay (WTP) for non-GMO and organic products. The results show that while awareness of GMOs is high, there is a significant gap in understanding, as many respondents struggled with basic genetic concepts. Public attitudes are generally neutral, with moderate concerns about health and environmental risks. Notably, males and those with a science background exhibit more favorable attitudes towards GMO. The WTP analysis reveals a stronger preference for paying premiums on organic products over non-GMO items, indicating a higher perceived value of organic agriculture. Public perception of GMOs’ contributions to SDGs is largely positive, particularly for enhancing food security (SDG 2) and alleviating poverty (SDG 1), though concerns remain regarding environmental sustainability (SDGs 14 and 15). These findings underscore the need for targeted educational initiatives and effective communication strategies to close knowledge gaps and build public trust in GMO regulation, which are essential for informed public discourse and maximizing GMOs’ potential in sustainable development.